Krajnskeh modric prebujenje - Dović, Marijan (Jezik in slovstvo, 2020)
The article deals with the beginnings of Slovenian secular poetry from the early manuscript fragments to the death of Valentin Vodnik and Žiga Zois (1819). The turning point that marked the beginning of the continuous development of secular poetry in Slovenian was the publication of the Pisanice almanac (1779-1781) in the circle of Marko Pohlin (1735-1801) in Ljubljana. The major poets of this period are Anton Feliks Dev (173-1786), Jurij Japelj (1744-1807), Žiga Zois (1747-1819), Anton Tomaž Linhart (1756-1795), Valentin Vodnik (1758-1819), Pavel Knobl (1765-1830), the "folk" poets Miha Andreaš (1762-1821) and Andrej Šuster-Drabosnjak (1768-1825), Štefan Modrinjak (1774-1827), Urban Jarnik (1784-1844) and Janez Nepomuk Primic (1785-1823). While some of them mainly wrote poetry for the common people (Knobl, Andreaš, Drabosnjak), for their own pleasure (Zois, Japelj) or failed to publish poems (Modrinjak, Primic), three of them in particular - Dev, Vodnik and Jarnik - can be considered poets in the modern sense of the word. A brief chronological overview attempts to incorporate recent findings about this period and, by analysing selected poetic passages, to demonstrate how the conventions characteristic of the modern literary system gradually developed and consolidated.
Keywords: Dev, Anton Feliks; Jarnik, Urban; Modrinjak, Štefan; Pisanice; Slovenian literature; Slovenian poetry; Slovenian secular poetry; slovenska književnost; slovenska poezija; slovenska posvetna poezija; Vodnik, Valentin; Zois, Žiga